Integrated application of geophysical loggings and fracture survey on rock exposures for identifying transmissive fractures in crystalline aquifer: case study in the city of São Paulo - Fiume,Bruna (2020)
ABSTRACT: The integrated analysis of geophysical loggings for identifying transmissive fractures has had a limited use in Brazil, although a large number of studies have been conducted so far throughout the world. The application of those tools has gained a crescent importance as they are needed for characterizing groundwater contamination in fractured rock aquifers at a great number of industrial sites worldwide and in Brazil. This paper presents the analysis of data collected by caliper, optical televiewer (OPTV), acoustic televiewer (ATV) and flowmeter loggings in four deep supply wells located in the industrial area of Jurubatuba, city of São Paulo. Five fracture sets (G1 through G5) were identified based on OPTV and ATV borehole loggings. The main fracture set (G1), NE-striking with low to intermediate dip, is subparallel to the foliation, being at great extent the result of the reactivation of this previous discontinuity. Fractures on ATV and OPTV images were visually classified with regard to flow evidence, and a positive correlation between high flow evidence and significant flow rate, measured by a flowmeter, was identified. On the other hand, the majority of fractures with insignificant, low or intermediate flow evidence are located in depth intervals with no significant flow rate. Fractures that belong to G1 are of major importance for flow, as in 9 of the 16 intervals with significant flow, they are the only fractures present. Data were inconclusive regarding transmissivity of high dip fractures, because few of them were intercepted by the well boreholes. However, there is evidence that subvertical fractures of sets G3 and G5, NE and NW striking, respectively, are also transmissive, which corroborates outcrop observations. Although geophysical loggings are essential to identify the most important segments of boreholes for water input and output, and to collect detailed data of low dip fracture sets at greater depths, the structural geology characterization of fractured aquifers cannot rely on borehole geophysical loggings alone. For proposing realistic conceptual models of the fracture network, data from boreholes should be complemented with data from large rock exposures (quarries), in order to describe geometrical parameters, such as spacing, length, and physical connectivity of low, intermediate and high dip fractures, as well as evidence of flow along individual fractures.